1998
DOI: 10.1080/02841859809172152
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary dimensions and volume measurements in pregnancy and post partum

Abstract: The pituitary gland enlarges in three dimensions throughout pregnancy. During pregnancy, the volume of the gland shows the highest percentage of increase compared to its length, height, and width. The maximum height of the gland does not exceed 10 mm during pregnancy but it may exceed 10 mm during the 3 days immediately post partum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 12 publications
0
53
0
1
Order By: Relevance
“…Correspondingly, the volume of the pituitary underlies pregnancy- and lactation-associated changes. Although the pituitary enlarges during the course of pregnancy, probably due to hyperplasia of PRL cells [62], it decreases up to eight month after delivery in humans [6365] or, respectively, seven days after delivery in rodents [6668], when the number of PRL cells reaches prepregnancy levels [69]. Similar effects have also been observed in the MPOA and SON of pregnant/lactating rats.…”
Section: Structural Functional and Molecular Plasticity Of The Bmentioning
confidence: 86%
“…Correspondingly, the volume of the pituitary underlies pregnancy- and lactation-associated changes. Although the pituitary enlarges during the course of pregnancy, probably due to hyperplasia of PRL cells [62], it decreases up to eight month after delivery in humans [6365] or, respectively, seven days after delivery in rodents [6668], when the number of PRL cells reaches prepregnancy levels [69]. Similar effects have also been observed in the MPOA and SON of pregnant/lactating rats.…”
Section: Structural Functional and Molecular Plasticity Of The Bmentioning
confidence: 86%
“…In earlier studies, an increase in pituitary volumes between 120 and 136% during pregnancy was found [6] (in comparison to nulliparous patients), with the largest volumes found immediately postpartum. A return to normal size between the first week and 6 months postpartum has been described [4,5]. Furthermore, an alteration of pituitary function by some drugs, which are frequently applied in late pregnancy, was found [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hormone-related factors such as the intake of estrogens and pregnancy are known to influence pituitary morphology [4,5,6,7]. However, little is known about pituitary size variations with short-term, transient and long-term changes of the hormonal status in women.…”
Section: Introductionmentioning
confidence: 99%
“…Pituitary apoplexy encompasses, but is not synonymous with, Sheehan's syndrome - a ischaemic infarction of the anterior pituitary gland resulting from postpartum haemorrhage 6. Profound postpartum hypotension is compounded by pituitary gland expansion of up to 136% by late pregnancy 7. Increase in size and associated changes in vascular supply and permeability may similarly precipitate haemorrhagic infarction during the antepartum period;5 8 however, these sequelae are rare and have only been documented in case reports 4 9…”
Section: Discussionmentioning
confidence: 99%